Activities of the Prevention Inspector to Ensure the Fulfillment of Restrictions Provided for in the Protection Order - Normatova Shirin Abdulnabievna (Scientific Trends, 2026)
This article analyzes issues related to the activities of the prevention inspector to ensure the implementation of restrictions stipulated in the protection order. In addition, this article sets out the issues of determining the activities of subjects in the rehabilitation of women who have suffered from harassment and violence, issuing them protection orders.
Keywords: Women, victims, physical, violence, prevention, inspector, protection order, mental, rehabilitation, legal documents.